Complementary feeding practice of mothers and associated factors in Hiwot Fana Specialized Hospital, Eastern Ethiopia - Semahegn, Agumasie (Pan Afr Med J, 2014)
INTRODUCTION: Malnutrition remains one of the main public health problems. Over one third of under-five mortality is caused by under nutrition related to inadequate complementary feeding. This study was aimed to assess of complementary feeding practice and associated factors. METHODS: Cross sectional study design was conducted to assess complementary feeding practice of mothers to their young children in Hiwot Fana specialized hospital in January 2013. Systematic sampling method was used to select 200 mothers to child pair to assess their timely initiation of complementary feeding and associated factors. Data were collected by using semi-structured questionnaire for face to face interview method. Descriptive statistics, binary and multiple logistic regressions were used for data analysis. RESULTS: The prevalence of timely initiate of complementary feeding was 60.5%. Nineteen percent of mothers were initiate complementary before 6 months. The reason for too early initiation of complementary feeding was lack of knowledge and perceive inadequate breast milk production by mothers 17(47.2%), 11(30.6%) respectively. Mothers have male child three times more likely timely initiate complementary feeding than female child (AOR 2.9,95% CI 1.2-7.3). This might be due to traditional gender norm that discriminate female feeding “female eat little talk little” this might start at early age life. CONCLUSION: More than half of them initiated complementary feeding timely which was low. The main reason reported by the mothers for early initiation of complementary feeding was lack of knowledge. Mothers who have male child were three times more likely timely initiate complementary feeding than female child. Information about importance of timely initiation of complementary feeding should be implemented via information education and behavioral change communications, and integrating with health extension package is recommended.